Analisis Kealpaan yang Mengakibatkan Matinya Orang Ditinjau dari Pasal 359 KUHP: Studi Kasus Putusan Perkara No. 952k/Pid/2010 - Yudi Anton Rikmadani (Jurnal Hukum dan Demokrasi (JHD), 2023)
The Criminal Code (KUHP) in force in Indonesia, regarding crimes that result in the death of a person is regulated in "Title XII Book II of the Criminal Code which contains two types of criminal acts, namely Article 359 of the Criminal Code in the form of "Because the mistake (culpa) caused the death of a person ”, with the threat of imprisonment for a maximum of five years or imprisonment for a maximum of one year, while Article 360 ​​of the Criminal Code states “Because of his mistake (culpa) causing a person serious injuries or such injuries, so that person becomes temporarily ill or unable to carry out his office. or temporary work. The Criminal Code contains coercive rules for every citizen if he violates these rules or commits a crime, anyone who violates them will face punishment. Moreover, for the perpetrators of crimes that kill other people's lives, and for the perpetrators will be given legal sanctions in accordance with their actions, thus in society will achieve a "Legal Protection", because legal protection can give a sense of security and peace with the existence of "Legal Certainty". Thus "Legal Protection" and "Legal Certainty" are two inseparable sides. Legal protection cannot be felt without legal certainty, on the contrary, with upholding legal certainty, legal protection will be enjoyed by the community.